Finite element studies on free vibration of laminated composite cylindrical skew panels - Srinivasa, Venkateshappa Chikkol; Suresh, Jayadevappa Y.; Prema Kumar, Wooday Puttiah (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents the finite element studies on free vibration of isotropic and laminated composite cylindrical skew panels. The analysis is performed using CQUAD4 and CQUAD8 elements of MSC/NASTRAN. The effects of the panel angle, skew angle, aspect ratio and length-to-thickness-ratio on fundamental frequency of isotropic cylindrical skew panels are studied. The effects of additional parameters such as the fiber orientation angle, numbers of layers and stacking sequence on the fundamental frequency of antisymmetric composite laminates are also studied.
Keywords: cylindrical skew panel; panel angle; skew angle; antisymmetric laminates; free vibrations; finite element; fundamental frequency